Spectral interrogation technique for tilted fibre Bragg Grating devices in refractometry and immunoassay / Waldo Udos - Waldo , Udos (2021)
Fibre Bragg grating (FBG) has been an important optical device since its discovery in 1978. Today, FBG is well known for its capability as a sensor and its wide-spread usage in various industrial and biomedical sectors. Tilted fibre Bragg grating (TFBG) is one of the FBGs that has superior sensitivity to ambient refractive index. This has attracted the curiosity and attention among the researchers. However, the comprehension and analysis for the sophisticated output spectrum of TFBG remains a challenge to researchers and users. Hence, there is a pressing need for the development of suitable and robust spectral interrogation technique for the TFBG’s output spectrum. Thus, as part of the research, its spectral interrogation technique in refractometry and immunoassay was studied. In this research, gold (Au) was deposited on TFBG to form gold-coated TFBG (Au-TFBG) by using the electron beam evaporation method. However, the ability to form an even thickness of gold film was limited due to the absence of a rotatory mechanism in the machine. Deposition schemes based on one-step, two-step and three-step deposition schemes were simulated and experimentally studied. The characteristics of deposition profile for each deposition scheme and remediation of shortcomings were discussed. The simulation was proven based on FESEM images of the deposited gold film on Au-TFBG. The characterization of the tilt plane of TFBG was studied to determine the effect of the uneven gold thickness to the optical transmission spectra of TFBG. The deposition angle, α was defined as the angle between the deposition direction and the tilt plane. The deposition angles of interest were 0º, 30º, 60º, 70º, 80º and 90º. It was worth noting that the deposition angle affected the transmission spectra of Au-TFBG in the aspect of the attenuation of cladding resonance in the longer wavelength range, cut-off wavelengths and the SPR resonance bandwidth. The optical transmission spectra of TFBG and Au-TFBG are complicated. It is hard to make data analysis due to the complexity of the spectrum. Besides that, the spectra characteristics depend on some fabrication parameters and affecting the technique of data acquisition. In this research, the optical transmission spectra was studied, and a new analytical method was developed to ease the signal demodulation. Lastly, Au-TFBG were employed as biosensors for the detection of EV-A71 virus, one of the causative agents for hand foot and mouth disease (HFMD). The biofunctionalization methods and the incorporation of Monoclonal antibodies (MAb) as the bio-receptor were introduced and discussed. It was noteworthy that MAb was responsible for the immobilization of EV-A71 virus and this contributed to the change in SPR mode intensity. LOD of the Au-TFBG was 0.343 × 10-6 g/ml. The bio-sensor was also proven to be sensitive to EV-A71 virus while non-reactive to other HFMD virus strains in the specificity tests.